Discovering Inclusivity in Remote Sensing: Leaving No One Behind - Joyce, Karen E.; Nakalembe, Catherine L.; Gómez, Cristina; Suresh, Gopika; Fickas, Kate; Halabisky, Meghan; Kalamandeen, Michelle; Crowley, Morgan A. (Frontiers in Remote Sensing, 2022)
Innovative and beneficial science stems from diverse teams and authorships that are inclusive of many perspectives. In this paper, we explore the status of inclusivity in remote sensing academic publishing, using an audit of peer-reviewed journal editorial board composition. Our findings demonstrate diversity deficiency in gender and country of residence, limiting the majority of editors to white men residing in four countries. We also examine the many challenges underrepresented communities within our field face such as implicit bias, harsher reviews, and fewer citations. We assert that in the field of remote sensing, the gatekeepers are not representative of the global society and this lack of representation restricts what research is valued and published, and ultimately who becomes successful. We present an action plan to help make the field of remote sensing more diverse and inclusive and urge every individual to consider their role as editor, author, reviewer, or reader. We believe that each of us have a choice to continue to align with a journal/institution/society that is representative of the dynamic state of our field and its people, ensuring that no one is left behind while discovering all the fascinating possibilities in remote sensing.